(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In clause the electronic - information society is considered, as evolutionary continuation of an industrial community, in which by the highest rates grow, connected with creation and consumption of the information, and the new information and communication technologies which have arisen as a result of technological, influence character of the communications.